Analysis of composite layered beams using Carrera unified formulation with Legendre approximation. (15th March 2018) - Arruda, M.R.T.; Castro, L.M.S.; Ferreira, A.J.M.; Garrido, M.; Gonilha, J.; Correia, J.R.
Abstract: This paper presents some numerical investigations related to the use of a new approximation function to be applied in Carrera's Unified Formulation (CUF). The main objective is to study and assess the efficiency of the CUF, when Legendre approximation functions are used at the section level, on 1D element, using an equivalent single layer (ESL) formulation. Previous experimental and analytical results, obtained in the case of GFRP composite bridge decks and sandwich panels, are used to further validate the numerical results being reported. 3D finite elements are also used, in order to compare and validate the numerical structural outputs. The main conclusion is that the classical Legendre polynomial functions are suitable and provide accurate results. The use of this type of functions does not require any stabilization procedure of the resulting governing system for the case of 1D elements, in clear contrast to what typically happens when other approximation functions are used with an equivalent single layer formulation.